Complexes of NiII, CoII, ZnII, and CuII with Promising Anti-Tuberculosis Drug: Solid-State Structures and DFT Calculations - Mohamed Ali Ahmed; Maksim A. Zhernakov; Edward M. Gilyazetdinov; Mikhail S. Bukharov; Daut R. Islamov; Konstantin S. Usachev; Alexander E. Klimovitskii; Nikita Yu. Serov; Vladimir A. Burilov; Valery G. Shtyrlin (Inorganics, 2023)
Four new NiII, CoII, ZnII, and CuII complexes with the promising anti-tuberculosis drug (E/Z)-N′-((5-Hydroxy-3,4-bis(hydroxymethyl)-6-methylpyridin-2-yl)methylene)-isonicotino-hydrazide (LH) were synthesized and characterized by structural methods: single-crystal X-ray diffraction, vibrational spectroscopy, and mass spectrometry. The NiII, CoII, and ZnII metal ions form only amorphous phases with various morphologies according to mass spectrometry and IR spectroscopy. The CuII forms a crystalline 1D coordination polymer with the relative formula <semantics><mmultiscripts>{[Cu<mstyle mathvariant="bold" mathsize="normal">L</mstyle>Cl]·0.5H2O}∞1</mmultiscripts></semantics>. Even though the LH ligand in the crystalline state includes a mixture of E-/Z-isomers, only the tautomeric iminol E-/Z-form is coordinated by CuII in the crystal. The copper(II) complex crystallizes in the monoclinic P21/n space group with the corresponding cell parameters a = 16.3539(11) Å, b = 12.2647(6) Å, and c = 17.4916(10) Å; α = 90°, β = 108.431(7)°, and γ = 90°. DFT calculations showed that the Z-isomer of the LH ligand in solution has the lowest formation energy due to intramolecular hydrogen bonds. According to the quantum chemical calculations, the coordination environment of the CuII atom during the transfer of the molecule into the solution remains the same as in the crystal, except for the polymeric bond, namely, distorted trigonal bipyramidal. Some of the complexes investigated can be used as effective sensors in biosystems.